2017
DOI: 10.1161/jaha.116.005066
|View full text |Cite
|
Sign up to set email alerts
|

Ketone Body Infusion With 3‐Hydroxybutyrate Reduces Myocardial Glucose Uptake and Increases Blood Flow in Humans: A Positron Emission Tomography Study

Abstract: BackgroundHigh levels of ketone bodies are associated with improved survival as observed with regular exercise, caloric restriction, and—most recently—treatment with sodium–glucose linked transporter 2 inhibitor antidiabetic drugs. In heart failure, indices of ketone body metabolism are upregulated, which may improve energy efficiency and increase blood flow in skeletal muscle and the kidneys. Nevertheless, it is uncertain how ketone bodies affect myocardial glucose uptake and blood flow in humans. Our study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
118
4
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 62 publications
5
118
4
6
Order By: Relevance
“…This likely reflects the high rates of β-oxidation and derivative acetyl-CoA production in the normal heart. The substrate competition results in the normal canine heart shown here differ from those of a recent report that described a reduction on cardiac glucose uptake with acute infusion of 3OHB in humans without HF (45). The basis for this discrepancy is unclear but could relate to species differences or the impact of acute versus chronic infusion of 3OHB.…”
Section: Discussioncontrasting
confidence: 94%
“…This likely reflects the high rates of β-oxidation and derivative acetyl-CoA production in the normal heart. The substrate competition results in the normal canine heart shown here differ from those of a recent report that described a reduction on cardiac glucose uptake with acute infusion of 3OHB in humans without HF (45). The basis for this discrepancy is unclear but could relate to species differences or the impact of acute versus chronic infusion of 3OHB.…”
Section: Discussioncontrasting
confidence: 94%
“…Ketones are considered to be more energy efficient under conditions of metabolic stress as they require less oxygen per molecule of ATP generated . In addition, ketone oxidation does not inhibit the oxidation of other substrates through the Randel cycle, and ketones appear to improve myocardial blood flow . A single dose of EMPA was recently shown to increase myocardial ATP, which was strongly correlated with the changes in circulating ketone levels .…”
Section: Discussionmentioning
confidence: 99%
“…In healthy humans, ketone body (3-hydroxybutyrate) has been shown to decrease myocardial glucose uptake and to elevate myocardial blood flow, suggesting that ketone bodies are crucial fuels for heart and ketone bodies work as vasodilators. This proposes potentials of ketone bodies for the treatment of heart failure (18), supporting the usefulness of SGLT2i for treatment of heart failure. In summary, the CVD-REAL study (6) showed a significant contribution of SGLT2i to a risk reduction in hospitalization for heart failure and all-cause death, and also proved that the benefits seen with empagliflozin in the EMPA-REG OUTCOME trial may be a class effect.…”
mentioning
confidence: 56%